SCCNV: A Software Tool for Identifying Copy Number Variation From Single-Cell Whole-Genome Sequencing - Dong, Xiao; Zhang, Lei; Hao, Xiaoxiao; Wang, Tao; Vijg, Jan (Frontiers in Genetics, 2020)
Identification of de novo copy number variations (CNVs) across the genome in single cells requires single-cell whole-genome amplification and sequencing. Although many experimental protocols of amplification methods have been developed, all suffer from uneven distribution of read depth across the genome after sequencing of DNA amplicons, which constrains the usage of conventional CNV calling methodologies. Here, we present SCCNV, a software tool for detecting CNVs from whole genome-amplified single cells. SCCNV is a read-depth based approach with adjustment for the whole-genome amplification bias. We demonstrate its performance by analyzing data obtained with most of the single-cell amplification methods that have been employed for CNV analysis, including DOP-PCR, MDA, MALBAC and LIANTI. SCCNV is freely available at https://github.com/biosinodx/SCCNV.